Assessing the impacts of COVID-19 on Myanmar’s economy: A Social Accounting Matrix (SAM) multiplier approach - Diao, Xinshen; Aung, Nilar; Lwin, Wuit Yi; Zone, Phoo Pye; Nyunt, Khin Maung; Thurlow, James (International Food Policy Research Institute, 2020)
The policy measures taken by the Government of Myanmar to contain the transmission of COVID-19 are a necessary and appropriate response to the pandemic. In-depth analysis of policy measures of this magnitude on firms, households, government, and the economy as a whole is key to the design of policy interventions that can mitigate the economic losses and support a sustained and robust recovery. In this policy paper, we use a Social Accounting Matrix (SAM) multiplier model to assess the effects of the COVID-19 pandemic on Myanmar’s economy. The SAM multiplier model is a simulation tool ideally suited to measuring short-term direct and indirect economy-wide impacts of unanticipated, rapid-onset economic shocks, such as COVID-19. The multiplier model builds on a SAM, which is a database that captures resource flows associated with all economic transactions taking place in an economy and represents the structure of the economy at a point in time by showing the interlinkages and relationships between actors, i.e., productive activities, households, governments, and relationships with the rest of the world. The Myanmar SAM captures 63 distinct activities or sectors to characterize Myanmar’s economy in 2019.